Autonomy and motivation: A dual-self perspective - Junichiro Ishida (Osaka University, Institute of Social and Economic Research (ISER), 2011)
This paper provides a simple autonomy-based model of human motivation in which a decision maker with divided selves must perform some task. The key presumption of the model is that the brain is not a unitary system which is equipped to achieve a single goal in a systematicmanner; rather, it ismore like an organizationwhich is hampered by several constraints such as preference incongruence and incomplete exchange (or imperfect recall) of information. Due to these constraints, themodel yields behavioral patterns that are consistent with various stylized facts of human motivation, mostly found in social psychology. The main findings of the paper are: (i) more autonomy induces more motivation; (ii) complex tasks are susceptible to motivation crowding out; (iii) small rewards are detrimental to motivation; (iv) intrinsically interesting tasks are susceptible to motivation crowding out.
Keywords: D03; D99; 330; Autonomy; Intrinsic and extrinsic motivation; Dual self; Motivation crowding out; Motivationstheorie; Sozialpsychologie